Characterization and uniqueness of equilibrium in competitive insurance - Vitor Farinha Luz (Theoretical Economics, 2017)
This paper provides a complete characterization of equilibria in a game-theoretic version of Rothschild and Stiglitz's (1976) model of competitive insurance. I allow for stochastic contract offers by insurance firms and show that a unique symmetric equilibrium always exists. Exact conditions under which the equilibrium involves mixed strategies are provided. The mixed equilibrium features (i) cross-subsidization across risk levels, (ii) dependence of offers on the risk distribution, and (iii) price dispersion generated by firm randomization over offers.
Keywords: C72; D43; D82; D86; G22; 330; Asymmetric and private information; mechanism design; oligopoly; economics of contracts; insurance